The Effect of Task-based upper Limb Training on Activities of Daily Living and Upper Limb Function in Chronic Stroke Patients (Medico Legal Update, 2020)
Background/Objectives: The goal of this study was to survey the influence on intervention of task-based upper limb training on activities of daily living and upper limb function in chronic stroke patients.Method/Statistical Analysis: 32 patients were randomly divided to into two groups. For the affected upper limb, the experimental group (N=16) applied the task-based training program (TBTP) and the control group (N=16) performed the non-task-based training (NTBT). Both groups executed 5 times per week, 30 minutes per session for 4 weeks. The paired t-test was used to compare before and after intervention results of each group. The independent t-test was used to compare changes in results between the groups.Findings: In the TBTP group, the pre-intervention of Fugl-Meyer assessment (FMA) is 46.75 ± 3.75 and the post-intervention score is 50.88±4.92. In the NTBT group, the FMA had a pre-intervention score of 47.44±4.44 and a post-intervention score of 49.13±5.14. Both groups showed statistically significant differences before and after intervention (p